Effects of acoustic stimulation intensity on air-conducted vestibular evoked myogenic potential in children - Xiao, Qianwen; Zhang, Qin; Wu, Qiong; Shen, Jiali; Wang, Lu; Chen, Yanfei; Lv, Jingrong; Yang, Jun; Jin, Yulian; Zhang, Qing (Frontiers in Neurology, 2022)
Objective: To investigate the effects of acoustic stimulation intensity on ocular and cervical vestibular evoked myogenic potential (oVEMP and cVEMP) elicited by air-conducted sound (ACS) in healthy children. Methods: Thirteen healthy children aged 4-10 years and 20 healthy adults aged 20-40 years with normal hearing and tympanometry were enrolled in this study. All subjects received oVEMP and cVEMP tests under different acoustic stimulation intensities (131, 126, 121, 116, 111 and 106 dB SPL). Mean n1 latency, p1 latency, interpeak latency, amplitude and response rate were investigated and analyzed. Results: As the acoustic stimulation intensity decreased, for oVEMP, the response rate of children decreased from 100% (131, 126 and 121 dB SPL) to 57.69% (116 dB SPL), 26.92% (111 dB SPL) and 11.54% (106 dB SPL). The response rate of adults decreased from 100% (131 and 126 dB SPL) to 95% (121 dB SPL), 55% (116 dB SPL), 12.5% (111 dB SPL) and 2.5% (106 dB SPL). There were significant differences in n1 latency, p1 latency and amplitude in both children and adults when comparing by acoustic stimulation intensities (p<0.05). Regarding cVEMP, the response rate of children decreased from 100% (131, 126 and 121 dB SPL) to 88.46% (116 dB SPL), 53.85% (111 dB SPL) and 26.92% (106 dB SPL). The response rate of adults decreased from 100% (131 and 126 dB SPL) to 95% (121 dB SPL), 85% (116 dB SPL), 37.5% (111 dB SPL) and 7.5% (106 dB SPL). A statistically significant difference was found in amplitude at different acoustic stimulation intensities in both children and adults (p<0.05). When stimulated by 131 dB SPL acoustic stimulation, there were significant differences in all cVEMP parameters and oVEMP n1 latency between children and adults (p<0.05). Conclusions: The response rate and amplitude of oVEMP and cVEMP in children and adults presented significant differences with a decrease in acoustic stimulation intensity. In this study, using 121 dB SPL for children and 126 dB SPL for adults during VEMP test could be regarded as safer stimulation intensities and thus reduced sound exposure.